A ruptured internal carotid artery aneurysm located at the origin of the duplicated middle cerebral artery associated with accessory middle cerebral artery and middle cerebral artery aplasia - Otani, Naoki (Medknow Publications, 2010)
BACKGROUND: Intracranial vascular anomalies involving the middle cerebral artery (MCA) are relatively rare, as such knowledge will be helpful for planning the optimal surgical procedures. CASE DESCRIPTION: We herein present the first case of a ruptured internal carotid artery aneurysm arising at the origin of the hypoplastic duplicated MCA associated with accessory MCA and main MCA aplasia, which was revealed by angiograms and intraoperative findings. CONCLUSION: In practice, this case highlights the urgent need to preoperatively recognize such vascular anomalies as well as understand the collateral blood supply in cerebral ischemia associated with these MCA anomalies.